Bone hydatid disease. Issue 982 (3rd August 2007) - Song, X H; Ding, L W; Wen, H
Abstract : Bone hydatid disease lacks a typical clinical appearance and image characteristics on x ray or CT are similar to those of tuberculosis, metastases and giant cell tumour or bone cysts. However, MRI does show distinctive diagnostic features of bone hydatid disease, especially in the spine. Until recently, treatment of osseous hydatid disease has been entirely surgical. Effective chemotherapy using benzimidazoles, particularly mebendazole, albendazole and combination treatments, has now been achieved in experimental studies and clinical practice. However, most of these drugs are still in the experimental stage or are in the early stages of clinical use.